2019
DOI: 10.1111/ocr.12311
|View full text |Cite
|
Sign up to set email alerts
|

Rapid maxillary expansion effects of nasal airway in children with cleft lip and palate using computational fluid dynamics

Abstract: The craniofacial morphology of children with unilateral cleft lip and palate (UCLP) differs from that of children without clefts. 1 Maxillary arch constriction is frequently observed in operated patients with UCLP. 2 Therefore, rapid maxillary expansion (RME) is often required in children with UCLP; in children without clefts, improvements in nasal airway ventilation and dentition expansion may be required. 3 However, improvements in nasal airway ventilation associated with RME in children with UCLP are unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
8
0
2
Order By: Relevance
“…Maxillary expansion improves mucociliary clearance and reduces rates of sinusitis in patients with cleft palate. 18,20 Our study supports previous findings that did not identify improvement in alar base symmetry following ABG alone. 21 However, our study showed that maxillary expansion may affect nasal symmetry.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Maxillary expansion improves mucociliary clearance and reduces rates of sinusitis in patients with cleft palate. 18,20 Our study supports previous findings that did not identify improvement in alar base symmetry following ABG alone. 21 However, our study showed that maxillary expansion may affect nasal symmetry.…”
Section: Discussionsupporting
confidence: 91%
“…15,16 Maxillary expansion can increase nasal ventilation, resolve nasal obstruction and reduce nasal pressure with widening at the internal nasal valve. [17][18][19] Trindade et al 3 used acoustic rhinometry to demonstrate patients with unilateral cleft lip and palate had improved nasal air flow following expansion. Maxillary expansion improves mucociliary clearance and reduces rates of sinusitis in patients with cleft palate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant improvements after RME in patients with CP/ CLP as observed in our study follow the results available in literature. Sing et al published a randomized controlled trial on 53 patients divided into two groups: patients with no cleft and patients with BCLP, both requiring maxillary expansion for correction of maxillary constriction and arch collapse [26]. The study showed that RME therapy had a statistically significant effect on improvements in hearing and function of the middle ear in both patients with no cleft and with BCLP with normal hearing levels and with mild conductive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…All written informed consents were received from the patients. The sample size was calculated based on an α of 0.05 and a β of 0.2 to detect the difference of 242.66 Pa in maximum pressure between groups, with a 300.22-Pa estimated standard deviation ( 29 ). The power analysis indicated that a sample size of 13 was required.…”
Section: Methodsmentioning
confidence: 99%